Validity and Reliability of the Persian Version of the Chronic Pain Grade Questionnaire in Patients with Musculoskeletal Pain - Soleymani, Ali; Masjedi Arani, Abbas; Raeissadat, Seyed Ahmad; Davazdahemamy, Mohammad Hasan (Advances in Nursing & Midwifery, 2019)
Introduction: Chronic pain which is a pain that remains or repeats for more than 3 to 6 months affects one in every 10 people in the world. Rising direct and indirect costs of chronic pain show the importance of researches which help to find better ways of pain management. Testing the validity and reliability of pain measurement tools in different populations can help this kind of researches. The chronic pain grade questionnaire is devised by Vonkorff and his colleagues. This seven-item instrument gives a score which empowers chronic pain patients to be characterized into one of four hierarchical categories according to pain severity or interference. The goal of this research was to test the validity and reliability of the Persian version of the chronic pain grade questionnaire. Methods: As a cross-sectional study after downloading the questionnaire from the internet and translating from English to Persian by researchers and backward translation by a native researcher, it was answered by 204 patients with musculoskeletal pain. These patients were referred to the physical medicine and rehabilitation clinic in Modarres Hospital and were registered using convenience sampling method. Patients were aged between 18 and 87; suffering from musculoskeletal pain (including primary and secondary pains) for at least the last 6 months. Fifty patients were reevaluated after two weeks. Results: As a result of testing reliability, Cronbach’s alpha was 0.89 and the Guttman split-half coefficient was around 0.82 and Test re-test coefficient using Spearman’s correlation coefficient was 0.89. Only a single component was extracted for the questionnaire, as a result of factor analysis. This component defines 59.8% of the variance. Conclusions: In summary, construct validity and reliability of the Persian version of the chronic pain grade questionnaire are approved, therefore it would be applicable to people with musculoskeletal pain in the Iranian population.